Test drive - Harte, Marie (Harte, Marie. Body shop bad boys., 2016)
The first in Harte's Body Shop Bad Boys series features a romance between heartbreaker Johnny Devlin, a mechanic son of a strip-club owner, and Lara Valley, a waitress in the local watering hole who is working to pay her way through nursing school. After several rejections, she agrees to go out with him after he saves her from her sister's groping ex, and discovers there's a lot more to him than she first thought. They enjoy each other and have glorious and inventive sex, yet Johnny is unable to believe that Lara could really want him for keeps.